Cacus and Marsyas in Etrusco-Roman legend. - Small, Jocelyn Penny, 1945- (Princeton monographs in art and archaeology, 2014)
This book discusses how Greek and South Italian vase paintings of the musical contest between Apollo and Marsyas became the model for Etruscan representations of Cacus ambushed by the Vibennae brothers, two Etruscan heroes of the sixth century B.C. The study demonstrates that the Etruscans knowingly adapted Greek iconographic forms to represent their own legends. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University.